2015
DOI: 10.1088/1748-0221/10/05/p05007
|View full text |Cite
|
Sign up to set email alerts
|

Development and underground test of radiopure ZnMoO4scintillating bolometers for the LUMINEU 0ν2β project

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…Thanks to highly-efficient α/β separation achieved by the Li 2 MoO 4 scintillating bolometers, we selected the α events to investigate the radioactive contamination of the crystals to be exhibited by α-active radionuclides from U/Th families. The performed analysis is similar to one described in details in [14]. As it is seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Thanks to highly-efficient α/β separation achieved by the Li 2 MoO 4 scintillating bolometers, we selected the α events to investigate the radioactive contamination of the crystals to be exhibited by α-active radionuclides from U/Th families. The performed analysis is similar to one described in details in [14]. As it is seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, choosing 0νDBD candidates with high Q-value, such as 82 Se or 100 Mo, provides a natural reduction of the background contribution from environmental γ's, that drops above the 2.6 MeV γ-line of 208 Tl. An extensive R&D activity allowed to characterize the properties of several compounds grown with such emitters, like ZnSe [21,22], ZnMoO 4 [23,24,25,26,27,28,29] or Li 2 MoO 4 [30,31,32,33,34]. These R&Ds demonstrated that the simultaneous read-out of light and heat in scintillating calorimeters enables a very effective suppression of the α background.…”
Section: Scintillating Cryogenic Calorimetersmentioning
confidence: 99%
“…Phonon-mediated cryogenic detectors using massive absorbers are a mature technology extensively employed in rare event physics experiments, like neutrinoless double beta decay (0νDBD) searches [1] (see for example CUORE [2], CUPID-0 [3], LUMINEU [4], AMoRE [5]...) and dark matter direct detection experiments [6,7] (EDELWEISS [8] , Super-CDMS [9], CRESST [10]...). Generally the working temperature is <100 mK and the most common phonon sensors are Neutron Transmutation Doped (NTD) Ge thermistors, which are glued to the detector surface and depending on the gluing characteristics are more or less sensitive to the ballistic component, or Transition Edge Sensors (TES), which usually are sensitive to the ballistic phonons.…”
Section: Introductionmentioning
confidence: 99%